Editorial techniques in the Hebrew Bible toward a refined literary criticism - Müller, Reinhard 1972-; Pakkala, Juha 1968- ([Erscheinungsort nicht ermittelbar] Society of Biblical Literature, 2021)
Cover -- Contents -- Abbreviations -- Introduction -- Additions: General Introduction -- Additions: Single Words and Short Phrases -- Additions: Single Sentences and Expressions -- Additions: Small Sections, Scenes, and Clusters of Connected Sentences -- Additions: Larger Passages -- Additions: Results -- Omissions -- Replacements -- Transpositions -- General Conclusions -- Bibliography -- Ancient Sources Index -- Modern Authors Index.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books